2008
DOI: 10.1111/j.1600-6143.2008.02327.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teriparatide on Early Bone Loss After Kidney Transplantation

Abstract: Kidney transplantation is associated with bone loss and a high risk of fractures. Prophylactic treatment of bone is therefore recommended in the early posttransplant period. As a large number of transplant recipients develop adynamic renal osteodystrophy, recombinant parathyroid hormone (rPTH) could be a promising therapeutic option.In a 6-month double-blind, randomized trial, 26 kidney transplant recipients were treated with daily subcutaneous injections of 20 lg teriparatide (PTH 1-34) or placebo. Bone miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 33 publications
0
46
2
2
Order By: Relevance
“…Recombinant parathyroid hormone (teriparatide) has also been evaluated recently 58. Its usefulness may be limited because of the secondary hyperparathyroidism commonly observed in long-term transplant recipients 46.…”
Section: Specific Types Of Osteoporosismentioning
confidence: 99%
“…Recombinant parathyroid hormone (teriparatide) has also been evaluated recently 58. Its usefulness may be limited because of the secondary hyperparathyroidism commonly observed in long-term transplant recipients 46.…”
Section: Specific Types Of Osteoporosismentioning
confidence: 99%
“…Alkaline phosphatase, osteocalcin, intact parathyroid hormone (iPTH), c-telopeptide pyridinoline crosslinks of type I collagen (CrossLaps), 25-hydroxycholecalciferol, calcitriol, calcium, and phosphate were quantified as described previously (15) according to Good Laboratory Practice standards.…”
Section: Serologic Parametersmentioning
confidence: 99%
“…A recent study of 26 kidney transplant recipients with daily teriparatide injections demonstrated a stabilization of BMD in the femoral neck and increased cortical width. But there was no improvement in bone turnover or bone mineralization as measured by histology (Cejka et al, 2008). Thus, its use in this setting remains experimental.…”
Section: Teriparatidementioning
confidence: 99%